The generations of the vaccines: Case of gastrointestinal antiparasitic vaccines used in Veterinary Medicine (Revista Sistemas de Producción Agroecológicos, 2021)
Vaccines are the fundamental pillar of preventive medicine and the basis for possible control and/or eradication of disease plans, especially infectious diseases. Internal parasites in production and companion animals continue to be one of the main threats to animal health and welfare with important economic implications, in addition to its impact on global public health. Its control has been based almost exclusively on chemotherapeutic drugs, which for several years have lost their efficacy and there are clear examples of parasitic resistance to them. Even so, few commercial examples of gastrointestinal parasite vaccines are commercially available for use in the practice of Veterinary Medicine. This review describes some commercial examples of gastrointestinal antiparasitic vaccines for their formulation in veterinary medical practice seen from the perspective of “the generations of vaccines'' and supported by experimental clinical studies of promising antigens for the prophylactic control of certain gastrointestinal parasitic agents of interest in public health mainly. To date, it is available with certain commercial limitations in some European and Australian countries Barbervax® and in South American countries Providean® Hidatil EG95 for use in ruminants for the control of Haemonchus contortus and Echinococcus granulosus, respectively; in some countries in America and Africa, Cysvax™ is available for the control of Taenia solium in pigs and in the world with very few limitations, a series of commercial vaccines for the control of coccidosis (Eimeria spp.) in poultry industry: turkeys, broilers and laying hens (e.g., CocciVac®, Immucox®, Paracox®, among others). There is a need to provide this type of vaccine to all countries where these gastrointestinal parasites are endemic and, in this way, provide options for their control. As well as a series of economic investments is highly necessary to support technical-scientific development around development of new effective and safe biologicals (new generations of vaccines) for the control of the most relevant internal parasites in production and companion animals.
Keywords: Internal parasite management; public health; zoonose